Psychometric evaluation of a social-emotional competence assessment instrument for high school students: Evidence of construct validity and reliability - Sri Rejeki Setiyorini; Wiwi Isnaeni; Saiful Ridlo (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2025)
Social Emotional Competence (SEC) was one of the essential competencies in 21st-century education, playing a crucial role in students’ personal and social development. However, valid and reliable instruments for assessing SEC for high school students in Indonesia were still limited. The instrument used in this study was adapted from the CASEL framework, which encompassed five core competencies: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. The adaptation process involved contextual and linguistic adjustments to align with the characteristics of Indonesian students. This study aimed to examine the validity and reliability of the adapted SEC assessment instrument. The research subjects consisted of 220 high school students in Demak who responded to a questionnaire. This study was categorized as descriptive quantitative. Construct validity was tested using CFA, while reliability was estimated using Cronbach’s alpha. The construct validity test produced model feasibility indices with CFI = 0.928, TLI = 0.9109, SRMR = 0.0534, and RMSEA = 0.0601. These results indicated that the measurement model demonstrated good feasibility. Based on the CFA analysis, 25 items were declared valid. Of these, 22 items had loading factor values greater than 0.5, while three items had loading factor values below 0.5. Despite the lower factor loadings, these three items were retained because they represented essential indicators. However, the item statements were revised to improve clarity and better represent the intended construct. The internal consistency reliability test showed a Cronbach’s alpha coefficient of 0.942. Since the coefficient value exceeded 0.70, the instrument could be considered reliable.